Characterizing physical activity and food urban environments: a GIS-based multicomponent proposal. Issue 1 (December 2016) - Cebrecos, Alba; Díez, Julia; Gullón, Pedro; Bilal, Usama; Franco, Manuel; Escobar, Francisco
Abstract Background Healthier urban environments influence the distribution of cardiovascular risk factors. Our aim was to design and implement a multicomponent method based on Geographic Information Systems to characterize and evaluate environmental correlates of obesity: the food and the physical activity urban environments. Methods Study location comprised a socio-demographically average urban area of 12 contiguous census sections (≈16, 000 residents), in Madrid, Spain. We conducted on-field audits on all food stores and street segments. We designed a synthetic index integrating continuous measures of both environments, by kernel density analyses. Index ranges from 0 to 100 (least-most healthy). Results We found a heterogeneous distribution with 75 and 50 % of the area scoring less than 36.8 and 25.5, respectively. Census sections of study area were categorized by Jenks intervals as high, medium–high, medium–low and low. 41.0 % of residents lived in an area with a low score, 23.6 % medium–low and 31.1 % medium–high and 4.2 % in a high. Conclusion The proposed synthetic index may be a relevant tool to inform urban health interventions, providing a feasible way to integrate different measures of barriers and facilitators of healthy urban environments in terms of food and physical activity.